Comparison of Fusion Rates among Various Demineralized Bone Matrices in Posterior Lumbar Interbody Fusion - Sanghoon Lee; Dae-Woong Ham; Ohsang Kwon; Joon-Hee Park; Youngsang Yoon; Ho-Joong Kim (Medicina, 2024)
Background and Objectives: Posterior lumbar interbody fusion (PLIF) plays a crucial role in addressing various spinal disorders. The success of PLIF is contingent upon achieving bone fusion, as failure can lead to adverse clinical outcomes. Demineralized bone matrix (DBM) has emerged as a promising solution for promoting fusion due to its unique combination of osteoinductive and osteoconductive properties. This study aims to compare the effectiveness of three distinct DBMs (Exfuse®, Bongener®, and Bonfuse®) in achieving fusion rates in PLIF surgery. Materials and Methods: A retrospective review was conducted on 236 consecutive patients undergoing PLIF between September 2016 and February 2019. Patients over 50 years old with degenerative lumbar disease, receiving DBM, and following up for more than 12 months after surgery were included. Fusion was evaluated using the Bridwell grading system. Bridwell grades 1 and 2 were defined as ‘fusion’, while grades 3 and 4 were considered ‘non-fusion.’ Clinical outcomes were assessed using visual analog scale (VAS) scores for pain, the Oswestry disability index (ODI), and the European quality of life-5 (EQ-5D). Results: Fusion rates were 88.3% for Exfuse, 94.3% for Bongener, and 87.7% for Bonfuse, with no significant differences. All groups exhibited significant improvement in clinical outcomes at 12 months after surgery, but no significant differences were observed among the three groups. Conclusions: There were no significant differences in fusion rates and clinical outcomes among Exfuse, Bongener, and Bonfuse in PLIF surgery.